Evaluating the performance of surfactant and charcoal-based cleaning products to effectively remove PAHs from firefighter gear - Hossain, MD Tanjim; Girase, Arjunsing G.; Ormond, R. Bryan (Frontiers in Materials, 2023)
Firefighters regularly respond to fire scenes where a mixture of chemicals including volatile, semi-volatile, and nonvolatile compounds are present in smoke and soot. Polycyclic aromatic hydrocarbons (PAHs) are common contaminants at fire scenes that may be deposited on the gear and the individual firefighter. Laundering is a common approach for the decontamination of contaminated gear. Surfactants are widely used by firefighters during laundering to remove PAHs as they are generally non-toxic and biodegradable. The removal of PAHs depends on the surfactant types, chemistries, and concentrations. This study evaluated the effect of surfactant concentrations to remove persistent contaminants like PAHs from turnout gear. The cleaning performance of different types of surfactants was also evaluated. Outer shell fabrics were contaminated with a standard mixture of 16 PAH compounds, and two commercial detergents were used at different concentrations. Additionally, the cleaning efficacy of eight commercially available regular and charcoal-based cleaning products was also determined against PAHs at a single surfactant concentration. For the decontamination method, a bench-scale washing procedure simulating the National Fire Protection Assocation 1851 laundering process was used. The removal efficacy of high molecular weight (HMW) PAHs were found to be lower compared to the low molecular weight PAHs for any type or any concentration of detergent. Our research also showed that the recommended surfactant concentrations provided by detergent manufacturers can be ineffective at removing the HMW PAHs from heavily contaminated fabric. With 1 mL of detergent in a 100-mL bath, which is multiple times higher than recommended amount, only 40% of HMW PAHs were removed. The cleaning efficacy can be increased to above 90% by using higher concentrations of detergents. This research shows that firefighters may need to use a higher concentration of detergent than the recommended amount to effectively remove PAHs from the gear. All the regular and charcoal-based detergents were able to remove PAHs effectively from contaminated fabrics when a higher concentration of detergent was used.